Composite indicators of labour market regulations in a comparative perspective - Mariya Aleksynska; Sandrine Cazes (IZA Journal of Labor Economics, 2016)
Technological progress and the internet brought about new possibilities of creating, storing, exchanging, replicating, and using various kinds of data for research. This paper discusses some of the dangers embedded into the reuse of data produced by some institutions by other institutions through the combination and aggregation of initial data into various data products. To this end, we use an example of labour market regulations' indicators developed by the World Economic Forum, the International Institute for Management Development (IMD), and the Fraser Institute, which are all partly based on the World Bank Employing Workers Indicator. We document how these three indicators compare and identify both their common and specific limitations. For each of these indicators, the choice of subcomponents and of aggregate techniques results in different pictures of labour market regulations, despite the use of the overlapping initial sources of data. Our comparative exercise calls for continuous efforts to improve the indicators of labour market regulations, as well as for cautious use of such indicators for research and policy advice.
Keywords: J00; J8; Y1; 330